Did my genes make me do it - "Stroll, Avrum" (London, 2006)
World-renowned philosopher Avrum Stroll argues that there are some problems that neither scientists, theologians nor philosophers will ever be able to solve. To prove this, he tackles the key questions that have perplexed humanity for centuries, unravelling them to get to the heart of the matter. Examining the contributions from figures such as Aristotle, Einstein, Newton, and St. Augustine, the reader is taken on an enthralling journey through the realms of science, religion, ethics, and philosophy in order to explore the most fundamental questions of human existence.
Keywords: Philosophy